Preventive measures for banking supervision on money laundering (Search in the Gulf Commercial Bank) - حمد, محمد احمد; حسون, عمار هادي (Journal of Economics and Administrative Sciences, 2014)
The research aims to study and assess the effectiveness of preventive measures banking for the reduction of money laundering based on the checklist (Check list), which have been prepared based on the paragraphs of some of the principles and recommendations of international and Money Laundering Act No. 93 of 2004 and the instructions thereto, to examine and assess the application of these measures by Gulf Commercial Bank, which was chosen to perform the search.I've been a statement the concept of money laundering in terms of the definition and characteristics, stages and effects of political, economic and social as well as the nature of banking supervision in terms of the definition and the most important objectives and its importance was then assess the Bank's commitment to the chosen preventive measures control for the reduction of money laundering.One of the most important conclusions that have been reached are not sufficient knowledge of some indicators of bank workers suspected some banking transactions , in addition to the weakness of the bank 's commitment to sample some preventive measures for the prevention and reduction of money - laundering operations .The most important recommendations that the researcher recommended attention they should develop the skills of workers in the bank to pay attention to preventive measures in order to combat money laundering through rehabilitation and training , as well as the adoption of the Bank's management policies and mechanisms include the development of procedures for reporting any process suspected , as well as forcing employees to obtain full information about customers and identify their activities and their physical potential , with special tightening control on some of the activities and banking operations and movements of some accounts that arise around the doubts and private money transfers without obvious reasons .